2001
DOI: 10.1354/vp.38-5-528
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Reproduction of Severe Disease in CD/CD Pigs Concurrently Infected with Type 2 Porcine Circovirus and Porcine Reproductive and Respiratory Syndrome Virus

Abstract: Abstract. Three-week-old cesarean-derived colostrum-deprived (CD/CD) pigs were inoculated with porcine circovirus type 2 (PCV2, n ϭ 19), porcine reproductive and respiratory syndrome virus (PRRSV, n ϭ 13), concurrent PCV2 and PRRSV (PCV2/PRRSV, n ϭ 17), or a sham inoculum (n ϭ 12) to compare the independent and combined effects of these agents. Necropsies were performed at 7, 10, 14, 21, 35, and 49 days postinoculation (dpi) or when pigs became moribund. By 10 dpi, PCV2/PRRSV-inoculated pigs had severe dyspnea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
235
5
17

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 286 publications
(272 citation statements)
references
References 31 publications
12
235
5
17
Order By: Relevance
“…Animals were sampled once a week for 6 weeks (from 11 to 17 weeks of age in farms 1 and 3, and from 4 to 10 weeks of age in farm 2) to obtain serum and saliva samples. Selected ages of animals were different in each farm in order to include the period around the expected time of infection, as PCV2 infection typically affects pigs between 8 and 16 weeks of age (Harms et al, 2001), whereas PRRS infection has higher virus replication in animals of 4 to 8 weeks of age (Cho et al, 2006). Animals were vaccinated twice against Mycoplasma hyopneumoniae (Stellamune Mycoplasma, inactivated M. hyopneumoniae NL 1042, Pfizer Animal Health, Madrid, Spain; 1st and 3rd weeks of life) and twice against Aujeszky disease virus (Porcilis Begonia, Intervet, Caracas, Venezuela; at 11 and 14 weeks of age).…”
Section: Animalsmentioning
confidence: 99%
“…Animals were sampled once a week for 6 weeks (from 11 to 17 weeks of age in farms 1 and 3, and from 4 to 10 weeks of age in farm 2) to obtain serum and saliva samples. Selected ages of animals were different in each farm in order to include the period around the expected time of infection, as PCV2 infection typically affects pigs between 8 and 16 weeks of age (Harms et al, 2001), whereas PRRS infection has higher virus replication in animals of 4 to 8 weeks of age (Cho et al, 2006). Animals were vaccinated twice against Mycoplasma hyopneumoniae (Stellamune Mycoplasma, inactivated M. hyopneumoniae NL 1042, Pfizer Animal Health, Madrid, Spain; 1st and 3rd weeks of life) and twice against Aujeszky disease virus (Porcilis Begonia, Intervet, Caracas, Venezuela; at 11 and 14 weeks of age).…”
Section: Animalsmentioning
confidence: 99%
“…However, some recent studies have reported reproduction of the complete disease in specific-pathogen-free (SPF) piglets [1], and in cesarean-derived colostrum-deprived piglets [8,19] but with a non-purified preparation of PCV2. Moreover, the lesions were more acute when the PCV2 inoculates were combined with either porcine parvovirus (PPV) [3,21,22] or porcine reproductive and respiratory syndrome virus (PRRSV) [19]. The immunostimulation also influences the PMWS development [4,23,24,30].…”
Section: Introductionmentioning
confidence: 99%
“…It is possible that the severity of histopathologic lesions was the result of co-infection with PCV2 and PRRSV. In domestic pigs, PCV2 is the primary cause of PMWS, but concurrent PRRSV infection leads to more severe disease forms (Harms et al, 2001).…”
Section: Discussionmentioning
confidence: 99%